Psychotherapy During COVID-19: How the Clinical Practice of Italian Psychotherapists Changed During the Pandemic - Boldrini, Tommaso; Schiano Lomoriello, Arianna; Del Corno, Franco; Lingiardi, Vittorio; Salcuni, Silvia (Frontiers in Psychology, 2020)
Aims: Italy was one of the first countries to be significantly affected by the COVID-19 pandemic, determining a unique scenario for Italian psychotherapists to consider changing the modality in which they deliver treatment. The present study aimed at studying which factors related to psychotherapists and their clinical practice had a major role in predicting two main outcomes: (1) the rate of interrupted treatments during lockdown, and (2) psychotherapists’ satisfaction with the tele-psychotherapy modality. Methods: An online survey was administered to licensed psychotherapists (N = 306), who worked mainly as private practitioners, between April 5 and May 10, 2020 (i.e., the peak of the pandemic in Italy). Results: Psychotherapists reported that 42.1% (SD = 28.9) of their treatments had been interrupted, suggesting that Italy faced an important undersupply of psychotherapy during the lockdown. Using AIC model selection, we identified three predictors of the rate of interrupted treatments: (1) psychotherapists’ lack of experience with tele-psychotherapy prior to the lockdown, (2) their theoretical orientation (with CBT psychotherapists reporting a higher rate of interrupted treatments), and (3) patients’ lack of privacy at home, as reported to the psychotherapists. Furthermore, we found four predictors of psychotherapists’ satisfaction with the tele-psychotherapy modality: (1) the rate of interrupted treatments, (2) psychotherapists’ previous experience with tele-psychotherapy, (3) their beliefs about the compatibility of tele-psychotherapy with their theoretical orientation, and (4) their use of a video-conferencing modality, rather than telephone. Conclusion: The following recommendations can help policy makers, professional associations and practitioners in promoting the continuity of psychotherapy treatments during the COVID-19 outbreak and in future emergencies: i) disseminating training programs for practitioners on tele-psychotherapy; ii) supporting patients to pragmatically access a private space at home; iii) encouraging practitioners to use video-conferencing (instead of telephone) to deliver remote therapy, and; iv) increasing the acceptance of tele-psychotherapy amongst both clinicians and the general public.